Chewing lice from wild birds in northern Greece - Diakou, Anastasia; Pedroso Couto Soares, José Bernardo; Alivizatos, Haralambos; Panagiotopoulou, Maria; Kazantzidis, Savas; Literák, Ivan; Sychra, Oldřich (Parasitology international, 2017)
Greece represents an important area for wild birds due to its geographical position and habitat diversity. Although the bird species in Greece are well recorded, the information about the chewing lice that infest them is practically non-existent. Thus, the aim of the present study was to record the species of lice infesting wild birds in northern Greece and furthermore, to associate the infestation prevalence with factors such as the age, sex, migration and social behaviour of the host as well as the time of the year. In total 729 birds, (belonging to 9 orders, 32 families and 68 species) were examined in 7 localities of northern Greece, during 9 ringing sessions from June 2013 until October 2015. Eighty (11%) of the birds were found to be infested with lice. In 31 different bird species, 560 specimens of lice, belonging to 33 species were recorded. Mixed infestations were recorded in 11 cases where birds were infested with 2-3 different lice species. Four new host-parasite associations were recorded i.e. Menacanthus curuccae from Acrocephalus melanopogon, Menacanthus agilis from Cettia cetti, Myrsidea sp. from Acrocephalus schoenobaenus, and Philopretus citrinellae from Spinus spinus. Moreover, Menacanthus sinuatus was detected on Poecile lugubris, rendering this report the first record of louse infestation in this bird species. The statistical analysis of the data collected showed no association between parasitological parameters (prevalence, mean and median intensity and mean abundance) in two different periods of the year (breeding vs post-breeding season). However, there was a statistically significant difference in the prevalence of infestation between a) migrating and sedentary passerine birds (7.4% vs 13.2%), b) colonial and territorial birds (54.5% vs 9.6%), and c) female and male birds in breeding period (2.6% vs 15.6%).
Keywords: Animals; Wild passerine birds; Birds; Female; Prevalence; Amblycera; ženské pohlaví; Phthiraptera; Greece; druhová specificita; Passeriformes; divoká zvířata; Host-Parasite Interactions; nemoci ptáků; zavšivení; Species Specificity; interakce hostitele a parazita; Chewing lice; Lice Infestations; ptáci; Ischnocera; Bird Diseases; prevalence; Male; Animals, Wild; zvířata; mužské pohlaví; Mediterranean area; Řecko